Facile synthesis of nanoporous Fe2O3 with internal nanocavities for highly reversible lithium storage - Thuy-An Nguyen; Halim, Martin; Lee, Joong Kee; Lee, Sang-Wha (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
Citrate-capped magnetites (cit-Fe3O4) are electrostatically conjugated with 3-aminopropyl trimethox-ysilane (APS), forming APS-complexed Fe3O4 (A-Fe3O4). Atmospheric calcination induces the direct conversion of A-Fe3O4 into silica-coated Fe2O3 (Fe2O3@SiC2) while preserving its nanoscale dimension (similar to 15 nm). One-pot chemical etching of the Fe2O3@SiC2 leads to iron oxide particles (Fe2O3) with internal nanocavities, so called nanoporous Fe2O3. After 200 cycles at the current density of 100 mA g(-1), the nanoporous Fe2O3 delivers a high reversible capacity of similar to 700 mAh g(-1) without distinct capacity fading. The excellent cycling stability of the nanoporous Fe2O3 is attributed to the superior buffering effect contributed by its nanoscale dimension and multiple internal nanocavities inside particles, which significantly retard the pulverization process of iron oxide particles. The facile one-pot synthesis of the nanoporous Fe2O3 is an effective, inexpensive route in designing high-performance electrode materials for sustainable energy conversion and storage applications. (C) 2017 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: HIGH-PERFORMANCE ANODE; CORE-SHELL MICROSPHERES; HIGH-CAPACITY ANODES; ELECTROCHEMICAL PERFORMANCE; ION BATTERY; HOLLOW SPHERES; ALPHA-FE2O3 NANORODS; ELECTRODE MATERIALS; COMPOSITE ANODE; IRON-OXIDES